POLITIK HUKUM PENANGGULANGAN TINDAK PIDANA PERIKANAN - Eddy Rifai; Khaidir Anwar (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
The study examines the political response to the crime of fisheries law, where criminal offenses prevention fishery does not operate effectively so that the results can only be overcome small fishermen. The research method uses juridical normative and empirical research sites in Lampung Province. The results showed that the politics of law including the formulation of policy or legislation making, policy application and execution or implementation of the legislation and enforcement of criminal law. Legislation on fisheries contained in the Fisheries Act has adequate set of law enforcement against criminal acts fishery, but there are obstacles in the application and execution stages, such as barriers in terms of law enforcement, infrastructure and public awareness.